The Longer-Term Psychosocial Development of Adolescents: Child Development Accounts and the Role of Mentoring - Chan, Ko Ling; Lo, Camilla Kin Ming; Ho, Frederick Ka Wing; Zhu, Shimin; Lai, Simon Man Kin; Ip, Patrick (Frontiers in Pediatrics, 2018)
Objective: To examine the long-term development of adolescents who participated in the Child Development Fund (CDF), which was a community intervention that consisted of Child Development Accounts and mentorship components. Design: This was an evaluative study of the CDF community intervention and was conducted between January and June 2016 in Hong Kong. Participants: A total of 902 adolescents from low socioeconomic backgrounds participated in this study (552 in the CDF and 350 in the comparison group). All CDF participants completed the three-year CDF program between 2011 and 2015. Main outcome measures: We assessed different developmental aspects of the adolescents, including health in terms of health-related quality of life; behavioral problems; attitude in terms of hope; cognitive capacity in terms of schooling; and social aspects in terms of social support. Results: Compared to the non-participants, the CDF participants appeared to have fewer behavioral problems, higher levels of perceived social support, higher levels of hope, better understanding of academic subjects, higher levels of motivation to study, fewer school withdrawal behaviors, and better quality of life related to social functioning. The male gender moderated the program’s effect on hope. Results also show that higher levels of mentorship quality moderated the program’s effect on social support, hope, self-perceived understanding of academic subjects, and motivation to study. Conclusion: Adolescents who participated in the CDF program appeared to perform better than the non-participants in regard to behavioral, academic, attitudinal, and social aspects. Good quality of mentorship had a positive influence on the program’s effects. The CDF appears to be a promising program offering long-term and multi-dimensional benefits to participants.